The influence of size effects on the ordering of liquid crystals located on nanoribbon graphene - Agelmenev, M.E.; Bratukhin, S.M.; Polikarpov, V.V. (KU Publ, 2022)
Experiments on computer simulation of the behavior of polar nematic phenylpropargyl ethers of parachlorophyllens on the surface of graphene nanoribbon made it possible to reveal a number of regularities.The dynamics of molecules is studied when the dimensions of graphene change under the action of an electric field and temperature. As a research method, the method of molecular dynamics was used in the approximation of a liquid state of aggregation. The simulation was carried out in the atomistic approach. It was shown that the graphene nanoribbon and electric filed defines the self-assembly of the nematic liquid crystals molecules in the biaxial state. These states appear at the variation of the graphene nanoribbon ratio of width to length. It was found that in the clearing area the ordering of the parachlorophyllens starts to grow when the value of the ratio of width to length is 3: 1.
Keywords: nematic liquid crystals; graphene nanoribbon; computer modeling